Serological diagnosis of Chagas disease: Evaluation of cross reaction in patients with visceral leishmaniasis (Research, Society and Development, 2021)
In Brazil, there are several simultaneously endemic regions for leishmaniasis and Chagas disease and, as the causative agents both belong to the same family, Trypanosomatidae, they share several antigens, which at the time of serological diagnosis can promote cross reactions. Several authors have evaluated Chagas/leishmaniasis cross reaction in dogs, however few studies have made this question in humans. The objective of this study was to identify the possibility of cross reaction for the diagnosis of Chagas disease in patients with cured visceral leishmaniasis. Therefore, thirty serum samples from patients with cured visceral leishmaniasis at the Infectious Diseases Clinic of the Hospital Regional de Presidente Prudente, São Paulo were analyzed. The samples were evaluated using three serological kits for the diagnosis of Chagas disease: immunoenzymatic assay (ELISA), indirect immunofluorescence (IFI) and indirect hemagglutination (HAI). Of the 30 samples analyzed, only one patient's serum showed to be reagent in the IFI, however, the duplicate evaluated was not positive, as well as the ELISA and HAI results. In the present study, due to the reactivity for the IFI to present in only one marked T. cruzi, with its duplicate and other serological tests (ELISA and HAI) negative, we can conclude that the patient with visceral leishmaniasis presented a cross reaction for the diagnosis of Chagas disease.